Shared functions of plant and mammalian StAR-related lipid transfer (START) domains in modulating transcription factor activity - Schrick, Kathrin; Bruno, Michael; Khosla, Aashima; Cox, Paige N.; Marlatt, Sara A.; Roque, Remigio A.; Nguyen, Henry C.; He, Cuiwen; Snyder, Michael P.; Singh, Daljit; Yadav, Gitanjali (My University, 2015)
Background: Steroidogenic acute regulatory protein (StAR)-related lipid transfer (START) domains were first identified from mammalian proteins that bind lipid/sterol ligands via a hydrophobic pocket. In plants, predicted START domains are predominantly found in homeodomain leucine zipper (HD-Zip) transcription factors that are master regulators of cell-type differentiation in development. Here we utilized studies of Arabidopsis in parallel with heterologous expression of START domains in yeast to investigate the hypothesis that START domains are versatile ligand-binding motifs that can modulate transcription factor activity. Results: Our results show that deletion of the START domain from Arabidopsis Glabra2 (GL2), a representative HD-Zip transcription factor involved in differentiation of the epidermis, results in a complete loss-of-function phenotype, although the protein is correctly localized to the nucleus. Despite low sequence similarly, the mammalian START domain from StAR can functionally replace the HD-Zip-derived START domain. Embedding the START domain within a synthetic transcription factor in yeast, we found that several mammalian START domains from StAR, MLN64 and PCTP stimulated transcription factor activity, as did START domains from two Arabidopsis HD-Zip transcription factors. Mutation of ligand-binding residues within StAR START reduced this activity, consistent with the yeast assay monitoring ligand-binding. The D182L missense mutation in StAR START was shown to affect GL2 transcription factor activity in maintenance of the leaf trichome cell fate. Analysis of in vivo protein–metabolite interactions by mass spectrometry provided direct evidence for analogous lipid-binding activity in mammalian and plant START domains in the yeast system. Structural modeling predicted similar sized ligand-binding cavities of a subset of plant START domains in comparison to mammalian counterparts. Conclusions: The START domain is required for transcription factor activity in HD-Zip proteins from plants, although it is not strictly necessary for the protein’s nuclear localization. START domains from both mammals and plants are modular in that they can bind lipid ligands to regulate transcription factor function in a yeast system. The data provide evidence for an evolutionarily conserved mechanism by which lipid metabolites can orchestrate transcription. We propose a model in which the START domain is used by both plants and mammals to regulate transcription factor activity.
Keywords: Transcription; Steroidogenic acute regulatory related lipid transfer; StAR; Homeodomain; HD-Zip; Glabra2; Yeast; Arabidopsis; Mouse